Atribuição de causalidade em presos, amputados e cegos: aceitação e luta contra o infortúnio - Dela Coleta, José Augusto (1980)
This work has the following objectives: (a) to verify the processes of causal and responsibility attribution used by prisoners, blinds and physically handicapped individuals in accounting for the events that lee to their misfortune; (b) to determine the relationship between the attribution processes used by the subjects and their coping responses; (c) to asses the utility of the theories of 'desire for control', 'just world' and 'defensive attribution' in the explanation of the events by the subjects; (d) to determine the influence of self-esteem, belief in a just world, locus of control and religious feeling on the attribution process; .(e) finally, to compare actors and observers insofar as causal attribution to the misfortune events is concerned. The first part consists of a review of the main theoretical contributions to the phenomenon of causal attribution in social psychology as well as of the research work related to it; its length is justified by the inexistence of texts of such nature in Portuguese. The second part is dedicated to the analysis of the responses given to scales and questionnaires by 43 subjects put in jail for having committed homicide or for having assalted to steal property, 40 physically handicapped of upper or lower members, 35 blinds (congenital or acquired), and 138 observers matched in age, socio-economic status and school level to the actors. The results indicated differences in the attributional processes employed by subjects with different types of misfortunes, as well as in the utilization of principles that inspire the three attribution theories considered. Differences are also found when actors are compared with observers. The results further show the relationship between psychological variables measured and causal attribution, as well as the influence of such variables upon the process of coping with the misfortune.